Genotypic and phenotypic evolution in a patient with chronic myelomonocytic leukemia. (2019) - Geissler, Klaus; Jäger, Eva; Gurbisz, Michael
Abstract: The correlation of molecular and phenotypic evolution in individual patients with chronic myelomonocytic leukemia (CMML) is poorly investigated. The longitudinal follow up of a CMML patient for more than 10 years illustrates that the emergence of clones harboring mutations in TET2, SRSF2, RUNX1, MPL, NRAS, and finally in multiple genes, respectively, was mirrored by thrombocytopenia, thrombocytosis, myeloproliferation and transformation into acute myeloid leukemia. Moreover, molecular aberrations of the RAS genes were associated with markedly increased spontaneous in vitro myeloid colony formation which has been shown to be a functional indicator of RAS pathway hyperactivation.